Ethylenediamine in alkaline cooking of jute stick for producing dissolving pulp (Bangladesh Journal of Scientific and Industrial Research, 2015)
Jute stick is the woody portion of jute plant. It remains as the leftover after extracting the fibre. The ratio of the stick to fibre is about 2.5:1. For producing dissolving pulp, prehydrolysis is carried out prior to pulping to remove hemicelluloses from the lignocelluloses. In this investigation ethylenediamine (EDA) was used with the cooking liquor to remove hemicelluloses from the jute stick. Increasing EDA charge in soda and kraft liquor decreased pentosans content in the pulp. EDA in kraft liquor showed lower kappa number and pentosans content than in the soda-liquor. Prehydrolysis further improved cellulose content and kappa number of jute stick pulp with the sacrifice of pulp yield. The bleachability of soda-EDA pulp was inferoior to the kraft-EDA and prehydrolysed soda-EDA in ECF bleaching sequences. The final brightness of soda-EDA pulp was 85.1% and kraft-EDA pulp 89.7%. Degraded cellulose (R18-R10) in soda-EDA and kraft-EDA pulps was lower than prehydrolysed pulps. Dissolving pulp can be produced to 93% purity without prehydrolysis by reinforcing EDA in kraft liquor.Bangladesh J. Sci. Ind. Res. 50(1), 7-14, 2015